Strengthening Local Governance in Bangladesh Reforms, Participation and Accountability - Chowdhury, Shuvra (Public Administration, Governance and Globalization ;, 2018)
This book explores the impact of Bangladesh's Local Government Act of 2009 on the functioning of the local governments or Union Parishads (UP), with a particular emphasis on people's participation and accountability. Throughout the chapters, the authors review the existing legal framework of UP and its relation to social accountability, examine how much of the social participation is spontaneous and how much is politically induced, question the success of the Citizen's Charter and Right to Information acts as mechanisms for social accountability, and present suggestions to remedy some of the problems facing people's participation and accountability in the UP. This book fills existing gaps in the discourse by adding new information to the literature on development research and legal reforms in Bangladesh, specifically in how those legal reforms have led to strengthening or weakening people's participation in local government. The target audience for this book are students and researchers in Asian studies , international development studies, and public administration, as well as practitioners working in the local governments discussed. .